Social Movements and Protests in Macedonia: Between State-Building and Popular Demands from Below - Biljana VANKOVSKA (Bezbednosni Dijalozi, 2015)
The paper focuses on the legitimacy crisis in Macedonia through the prism of two contradictory tendencies: on one hand, for years international state-building has had democratic institution-building as a priority rather than building capacities for democratic policies; on the other hand, the upsurge of social movements and protests in 2014-2015 questioned not only the legitimacy of those on power but also demanded radical shift of the political and social agenda. The protracted political crisis (2012-2015) has demonstrated the contradictory nature of the top-bottom and bottom-up political tendencies. The system that had been set up through exclusive input of the political elites under the auspices of the international community is now challenged by new participatory political forms of citizens’ engagement. The key question set in this paper reads: is Macedonian Spring possible under the constraints of the international state-building and what effect would one expect from such a political turnabout?